The Resilience of MSMEs During COVID-19 Pandemic: An Analysis Using Philip Kotler's Approach - Azhar, Neng Zulfa; Rahayu, Meilia Sri (Journal of Business Management, 2024)
This study explores the impact of the Covid-19 pandemic on the business continuity of micro, small, and medium-sized enterprises (MSMEs), specifically within the food sector. The research adopts a case study approach, analyzing how Bittersweet strategically used advertising during the crisis. The findings highlight the crucial role of advertising techniques in influencing consumer behavior, showing how effective promotional strategies can lead to sustained business growth during difficult times. By aligning promotional activities with changing consumer needs, Bittersweet strengthened its marketing efforts, enhancing customer loyalty and brand visibility. It suggests that MSMEs should focus on leveraging digital platforms to reach broader audiences and enhance customer engagement, especially during uncertain times. The success of Bittersweet demonstrates the potential for MSMEs to not only survive but thrive through strategic marketing adaptation, ensuring long-term resilience in the face of future challenges.